O processo decisório para obtenção de materiais de emprego militar no Exército Brasileiro - Lima, Flávio da Costa (2007)
This work has the objective to describe how the rational, organizational and political factors influence the military use material obtainment decision-making process in Brazilian Army. The approach proposed by Allison to analyze the Cuban Missile Crisis in 1962 had been used. The rational factors used were: calculus, value maximization, impersonality, rational choice and bounded rationality. The organizational factors were: organizational patterns and process, problem segmentation, centralized coordination and control, limited flexibility, predictability and organizational culture. The political factors used were: conflict, power, negotiation, contingency, cooptation, interests and external influence. The outcomes allowed verify that decision-making process, even happening in a rational based organization, is influenced by organizational and political process.